2020
DOI: 10.3892/ol.2020.11507
|View full text |Cite
|
Sign up to set email alerts
|

circ_103809 promotes breast cancer progression by regulating the PI3K/AKT signaling pathway

Abstract: Breast cancer is one of the most common cancer types in the world. This study was carried out to investigate the functional role of circular RNA circ_103809 in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
(15 reference statements)
4
15
0
Order By: Relevance
“…Furthermore, upregulation of hsa_circRNA_103809 increased cisplatin-resistance in CS-NSCLC cells, implying that targeting hsa_circRNA_103809 could potentially improve cisplatin-sensitivity in NSCLC cells. Previous data suggested that hsa_circRNA_103809 acted as an oncogene to promote cancer progression [15,19,18,16,17] , and this study evidenced that hsa_circRNA_103809 also modulated drug resistance in NSCLC, which broadened our knowledge in this eld.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, upregulation of hsa_circRNA_103809 increased cisplatin-resistance in CS-NSCLC cells, implying that targeting hsa_circRNA_103809 could potentially improve cisplatin-sensitivity in NSCLC cells. Previous data suggested that hsa_circRNA_103809 acted as an oncogene to promote cancer progression [15,19,18,16,17] , and this study evidenced that hsa_circRNA_103809 also modulated drug resistance in NSCLC, which broadened our knowledge in this eld.…”
Section: Discussionsupporting
confidence: 65%
“…Consistently, upregulation of hsa_circRNA_103809 increased cisplatin-resistance in CS-NSCLC cells, implying that targeting hsa_circRNA_103809 was feasible to improve cisplatin-sensitivity in NSCLC cells. Previous data suggested that hsa_circRNA_103809 acted as an oncogene to promote cancer progression [14][15][16][17][18], and this study evidenced that hsa_circRNA_103809 also modulated drug resistance in NSCLC, which broadened our knowledge in this eld.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, researchers found that continuous long-term cisplatin stimulation caused alteration of multiple cancer associated Circular RNAs (circRNAs) in NSCLC cells, resulting in cisplatin-resistance in cancer cells, which made cisplatin "ineffectiveness" to eliminate NSCLC cells [12,13], and uncovering the underlying mechanisms might solve this problem. Based on the above information, by searching the online Pubmed database (https://pubmed.ncbi.nlm.nih.gov/), we selected hsa_circRNA_103809 for further investigations in this study, and the main reason is that hsa_circRNA_103809 acted as an oncogene to promote cancer development in colorectal cancer [14], breast cancer [15], hepatocellular carcinoma [16], gastric cancer [17] and lung cancer [18]. However, up until now, the role of hsa_circRNA_103809 in regulating drug resistance in cancer treatment is still largely unknown, which made this issue become valuable and meaningful.…”
Section: Introductionmentioning
confidence: 99%
“…*P < 0.05 cisplatin-resistance in CS-NSCLC cells, implying that targeting hsa_circRNA_103809 could potentially improve cisplatin-sensitivity in NSCLC cells. Previous data suggested that hsa_circRNA_103809 acted as an oncogene to promote cancer progression [15][16][17][18][19], and this study evidenced that hsa_circRNA_103809 also modulated drug resistance in NSCLC, which broadened our knowledge in this field.…”
Section: Discussionsupporting
confidence: 59%
“…Uncovering the underlying mechanisms leading to this resistance might solve this problem. Based on the above information, by searching the online Pubmed database (https://pubmed.ncbi.nlm.nih.gov/), we selected hsa_circRNA_103809 for further investigations in this study, and the main reason is that hsa_circRNA_103809 acted as an oncogene to promote cancer development in colorectal cancer [15], breast cancer [16], hepatocellular carcinoma [17], gastric cancer [18] and lung cancer [19]. However, to date, the role of hsa_circRNA_103809 in drug resistance in cancer remains largely unknown and therefore important to investigate.…”
Section: Introductionmentioning
confidence: 99%